Phytochemicals of Natural Products Analysis and Biological Activities - Mihaylova, Dasha; Popova, Aneta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The plant kingdom, with its terrestrial and marine natural products, has been widely explored. Plant-based products have long been used to prevent and treat various ailments. Many natural compounds have been reported to have a variety of interesting and significant biological activities, including antioxidant, anti-inflammatory, antitumor, antibacterial, antiviral, antifungal, antiparasitic, analgesic, antidiabetic, anti-atherogenic, and antiproliferative, as well as cardioprotective and neuroprotective properties. Therefore, researchers pay special attention to the bioactive compounds synthesized by plants. Opportunities in functional ingredients and treatment of NCDs (oxidative stress, diabetes, obesity, metabolic syndrome, etc.) are widely explored. However, many therapeutic properties of plants are still to be discovered. This Special Issue reprint intends to substantially contribute to our knowledge of their beneficial properties. Natural products could be a vast resource in respect of human well-being improvement. This Special Issue reprint also aims to disseminate some of the most recent and significant contributions in natural product research on phytochemicals and biological activity.